How to Win a Cosmic War : Confronting Radical Islam - Aslan, Reza (London William Heinemann, 2009)
Lays out, for the first time, a comprehensive definition of the movement behind and surrounding al-Qaeda and the like, a global ideology properly term Jihadism.
Include Bibliography and Index
Keywords: Islamic fundamentalism -- Jihad -- Globalization -- War on Terrorism, 2001-2009